Identification of Listeria monocytogenes Contamination in a Ready-to-Eat Meat Processing Plant in China - Zhang, Hongzhi; Que, Fengxia; Xu, Biyao; Sun, Linjun; Zhu, Yanqi; Chen, Wenjie; Ye, Yulong; Dong, Qingli; Liu, Hong; Zhang, Xi (Frontiers in Microbiology, 2021)
Listeria monocytogenes is the etiologic agent of listeriosis, which remains a significant public health concern in many countries due to its high case-fatality rate. The constant risk of L. monocytogenes transmission to consumers remains a central challenge in food production industry. At present, there is very little known about L. monocytogenes contamination in ready-to-eat (RTE) processing plants in China. In this study, L. monocytogenes in an RTE meat processing plant in Shanghai municipality was characterized using pulse-field gel electrophoresis (PFGE) and whole genome sequencing (WGS). Furthermore, the biofilm formation ability of the pathogen was also tested. Results revealed that L. monocytogenes isolates were present in 12 samples out of the 47 samples investigated. Most of them ((75%, 9/12) were identified from the processing facilities irrespective of observed hygiene levels of PAC and coliforms, which were present in only one processing facility. ST5 (1/2b) isolates were predominant (83.3%, 10/12), and were identified in two dominant PTs (five in PT1 and four in PT3, respectively). Results of the core-genome multi-locus sequencing typing (cgMLST) showed that ST5 in PT1～3 had 0～8 alleles, which confirmed that clonal transmission occurred in the RTE meat processing facilities. In addition, the biofilm formation test confirmed that the isolates from processing facilities could form biofilms, which helped them colonize and facilitate persistence in the environment. These results indicated that common sanitation procedures regularly applied in the processing environment were efficient but not sufficient to remove L. monocytogenes isolates. Furthermore, the ST5 isolates in this study exhibited 12 alleles with one ST5 clinical isolate, which contributes to the understanding of the potential pathogenic risk that L. monocytogenes in RTE meat processing equipment posed to consumers. Therefore, strong hygienic measures, especially sanitation procedures for biofilms eradication, should be implemented to ensure the safety of raw materials. Meanwhile, continuous surveillance might be vital for the prevention and control of listeriosis caused by L. monocytogenes.